Implementation of Occupational Health and Safety (OHS) Policy: A Case Study of the Disparity Between PPE Regulations and Field Practices Among Live-Line Maintenance Workers (PDKB) at PT PLN (Persero) UP3 Sukoharjo - Tiara Indah Banuwati; Syefira Ayudia Johar; Nur Ani; Wartini (International Journal of Health and Pharmaceutical (IJHP), 2026)
Introduction: This study analyzes the disparity between Personal Protective Equipment (PPE) regulations and field practices among Live-Line Maintenance workers (PDKB) at PT PLN (Persero) UP3 Sukoharjo. The research was motivated by a fatal incident in Lubuk Pakam in 2023 and three near-miss incidents at the research location caused by negligence in the use and supervision of PPE. Research Method: This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with five informants selected purposively (technicians, preparators, team leaders, and OHS officers), field observations, and documentation review. The data were analyzed using the Miles and Huberman model. Data validity was ensured through source and method triangulation. Research Results: The findings indicate a strong organizational commitment through the provision of internationally standardized PPE, certified training, periodic testing every six months, and multi-layered supervision in accordance with Law No. 1/1970, Government Regulation No. 50/2012, and Minister of Manpower Regulation No. 8/2010. The level of worker compliance is relatively high due to awareness of the risks associated with 20 kV electrical voltage and the safety culture of “one opens, three remind,” with PPE internalized as a “second life.” However, two main disparities were identified. First, PPE storage in operational vehicles and basecamps has not yet met the ideal standard of controlled storage facilities; this condition is compensated through adaptive mechanisms such as special storage boxes, air-conditioned rooms, and psychological ownership among workers. Second, regarding PPE materials, safety sleeves that should be made of insulating rubber are still made of plastic due to previous procurement. The multi-layered supervision system, supported by peer monitoring, has proven effective in detecting three near-miss incidents before they escalated into fatal events. Conclusion: This study concludes that the effectiveness of OHS implementation is not solely determined by formal compliance based on regulations (rules-based approach), but also by organizational safety culture (safety culture-based approach) and the synergy of social capital. Recommendation: The study recommends accelerating the transition to PPE that meets current standards, improving storage facilities, and strengthening the quality of double-check procedures.